2022
DOI: 10.1002/jcph.2066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voriconazole Exposure on the Pharmacokinetics of Tacrolimus in Lung Transplantation Patients, Based on Therapeutic Drug Monitoring Data

Abstract: Tacrolimus and voriconazole are usually used simultaneously in lung transplantations. Voriconazole can increase tacrolimus concentrations by inhibiting the cytochrome P450 (CYP) enzyme, which poses a great challenge for dose adjustment. The aim of this study is to clarify the correlation between voriconazole exposure and tacrolimus trough concentrations (C0), and to establish a population pharmacokinetic model including voriconazole trough concentrations (VOZ) as a covariate for dose optimization. All data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
0
3
Order By: Relevance
“…However, tacrolimus CL/F in the current study was inconsistent with two previous pharmacokinetic studies 37,38 . Chen et al reported that the typical CL/F value was 6.54 L/h, which was much lower than the value obtained in our study (12.85 L/h) after adjusting for tacrolimus daily dose and haematocrit 37 . However, the previous study calculated the CL/F value after 86 POD (ranging from 5 to 937 days), which may explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, tacrolimus CL/F in the current study was inconsistent with two previous pharmacokinetic studies 37,38 . Chen et al reported that the typical CL/F value was 6.54 L/h, which was much lower than the value obtained in our study (12.85 L/h) after adjusting for tacrolimus daily dose and haematocrit 37 . However, the previous study calculated the CL/F value after 86 POD (ranging from 5 to 937 days), which may explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed over 10-fold differences in AUC 0 − 12h between patients taking the same tacrolimus dose, highlighting the importance of close monitoring of tacrolimus blood concentration. However, tacrolimus CL/F in the current study was inconsistent with two previous pharmacokinetic studies 37,38 . Chen et al reported that the typical CL/F value was 6.54 L/h, which was much lower than the value obtained in our study (12.85 L/h) after adjusting for tacrolimus daily dose and haematocrit 37 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A detailed comparison of pharmacokinetics characteristics and patients' demographics among these studies is presented in Table 4. Chen et al, reported that the typical CL/F value of tacrolimus was 6.53 L/h, much lower than that in our study after adjusting for weight, tacrolimus daily dose, and haematocrit [34]. However, in their study, the enrolled patients were a median of 86 days posttransplant (ranging from 5 to 937 days).…”
Section: Discussioncontrasting
confidence: 73%
“…In our study, the median value of T max was 2 h, which was consistent with previous findings in patients soon after lung transplantation [4] and indicated rapid tacrolimus absorption. However, the geometric mean value of CL/F for tacrolimus was 9.95 L/h, which was larger than those in two previous pharmacokinetic studies in Chinese [34,35] and lower than that in Caucasians [36]. A detailed comparison of pharmacokinetics characteristics and patients' demographics among these studies is presented in Table 4.…”
Section: Discussionmentioning
confidence: 75%